Why Poor Organ Donation? A survey with Focus on Way of Thinking and Orientation About Organ Donation Among Clinic Attendees and Dialysis Patients Relatives. (August 2017) - Patel, Mohan; Balwani, Manish; Ugale, Prakash; Jadhav, Charusheela; Govardhane, Pravin; Wani, Kishore; Vilekar, Nandan; Patil, Dilipsingh; Sarswat, Vijay
Abstract : Introduction: Donor organ shortage is the greatest challenge facing the field of organ transplantation today. This study was conducted to evaluate awareness and attitudes toward organ donation in the community and to obtain information to improve national organ donation awareness campaign. Methods: We have conducted a randomized survey among 900 clinic attendees and kin of patients on dialysis. The study was conducted to evaluate the way of thinking, orientation and awareness toward organ donation at a tertiary care medical hospital in western India. A standard questionnaire, based on previously published questionnaires was used to test awareness and attitude and demographics. Results: Respondents were 60% male and 40% female and the age ranges from 35 to 75 years. Majority were from the age group of 35-50 years. Of the 900 attendees, ninety percent of them were married and 85% were Hindus. About 85% of them were aware about organ donation, but 44.2% of them were unaware about organ donation law. 32% of people heard about organ donation from the doctor or hospital brochures. Information was also obtained from the television (12.4%), newspaper (24.8%) and internet (4%). 12% of the people came to know about organ donation through friend/family. As many as 73.6% of respondents would like to donate organ if qualified for it, while 7% replied they can't say. About 19.4% said no to organ donation and all were males. The main concern to avoid donation was fear of disfigurement (22.4%), followed by religious beliefs (16.2%) and fear of misuse (9.4%). About 52% of people didn't mention reason for denial. All the attendees feel that the organs should be given to the needy patients irrespective of religion and priority be given to younger patients. About 90% said that the organ donor card must be considered a legal document. Conclusion: Our study reflects the lay public view point in the Indian community about the organ donation. The lack of information regarding on organ donation is the most important factor for low donation rates in India. To increase the actual donation, mass media like television, radio, newspapers, social networking sites and magazines should be utilized and emphasis should also be placed on religious and political leaders in removing social and religious beliefs. Government should also take the step considering legality of organ donor cards. Prof. Pankaj Shah, Prof. Vivek Kute .